An Empirically Grounded Eco-Sufism Model: Lived Experiences of Muslim Eco-Enzyme Practitioners in Palembang - Azrianti Ishamiyah; Kongo Iskandar Dinata; Umi Nur Kholifah (Journal of Sufism and Psychotherapy, 2026)
Abstract Urban ecological degradation increasingly affects not only environmental sustainability but also psychological well-being and spiritual life. Although eco-Sufism has been widely discussed within Islamic environmental ethics, empirical research examining how it is experienced through everyday ecological practice remains limited. This study aims to develop an empirically grounded Eco-Sufism Model by exploring how Muslim eco-enzyme practitioners construct spiritual meaning through ecological practice. A qualitative phenomenological design employing Interpretative Phenomenological Analysis (IPA) was used. Data were collected from ten Muslim eco-enzyme practitioners in the Siring Agung Subdistrict of Palembang through semi-structured interviews, participant observation, and four-week reflective documentation. The analysis identified three interconnected experiential dimensions. Tajalli al-Māddī represents spiritual awareness emerging through the material transformation of household organic waste; Tajalli al-Zamānī describes spiritual formation through waiting, uncertainty, and trust during the fermentation process; and Tajalli al-Takāmulī reflects an integrated awareness of the relationship between God, humanity, nature, and community. Together, these dimensions constitute an empirically grounded Eco-Sufism Model demonstrating how everyday ecological practice may simultaneously foster spiritual formation, psychosocial resilience, and ecological consciousness. By reconstructing eco-Sufism inductively from participants' lived experiences rather than normative theological discourse, this study contributes to eco-Sufism scholarship, Islamic psychology, and spiritual ecology while offering a conceptual framework for faith-based environmental education and community sustainability initiatives.